A robust method for increasing Fc glycan high mannose level of recombinant antibodies. Issue 6 (17th April 2015) - Huang, Chung‐Jr; Lin, Henry; Yang, Jerry (Xiaoming)
ABSTRACT High mannose (HM) glycoforms on antibody Fc glycan are recognized as critical quality attributes for therapeutic antibody products. Methods to control HM have been largely empirical, and it is challenging to target a desired HM level during antibody process development. A novel and robust method to increase antibody HM glycoforms is demonstrated in this study using multiple antibodies and cell lines without adversely impacting cell culture performance, including viable cell density, viability, and protein titer. This approach utilizes mannose as a carbon source and the ratio of mannose to total hexose (glucose and mannose) in feed media determines the extent of HM glycan content of an antibody expressed in cell culture. Scale‐up of this strategy from 3 mL small scale plate to bioreactor (1.5 L) is also demonstrated with comparable results. Further full glycan map analysis shows that HM increase predominantly correlates with the decrease in G0F glycan, with minimum impact on other glycoforms. Possible hypotheses for the HM glycan modulation using mannose as carbon source are also discussed. Three pathways, including GDP‐mannose biosynthesis, early protein glycosylation and UDP‐N‐acetylglucosamine biosynthesis, might be involved and contribute to this HM modulation. Biotechnol. Bioeng. 2015;112: 1200–1209. © 2015 Wiley Periodicals, Inc.